Media in situations of conflict roles, challenges, and responsibility - Mbaine, Adolf E. (Fountain Publishers, 2006)
The role of the media and media reportage is crucial to any conflict situation. In Uganda, the Department of Mass Communication at Makerere University has endeavoured to support constructive reporting of the various conflicts that have beset the country and the region in the past decades. As part of this effort, it has organised lectures and commissioned research by media professionals and academic observers, whose work is brought together in this collection of essays.